PENGARUH TERAPI RELAKSASI TERHADAP KONTROL GLIKEMIK PADA PASIEN DIABETES MELLITUS DI PURWOKERTO - Wahyu Ekowati; Asep Iskandar; Made Sumarwati (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2013)
ABSTRACT Introduction : Diabetes mellitus is a condition that occurs when the body can't use glucose normally. Glucose is the main source of energy for the body's cells. The levels of glucose in the blood are controlled by a hormone called insulin, which is made by the pancreas. Insulin helps glucose enter the cells. Objective : to know the influence of relaxation therapy to reduce levels of glucose in the blood of diabetes mellitus in South of Purwokerto. Methode : Quasy experiment with device of research of pre-test-post-test with control group. Statistic analisys used this research is statistical analysis paired t-test. Result : The average of pre-test and post test control are 148,93 and 141,20. Result test paired samples t-test p value 0,420. The average of pre-test and post test experiment are 211,07 and 209,53. Result test paired samples t-test p value 0,957. Conclusion : Relaxation therapy has not influence to reduce levels of glucose in the blood of diabetes mellitus. Keyword : Diabetes mellitus, the levels of glucose in the blood, relaxation therapy